Applying TAM approach to investigate the adoption of mobile banking among Indian students - et. al., Amitabh Mishra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study in hand investigated factors affecting the adoption of mobile banking services among University students in India. Total 466 undergraduate university students were interviewed at various University campuses in five major cities of national capital region (NCR) of India. The study used factor analysis to identify factors determining the adoption of mobile banking among undergraduate university students in India. Further, it used regression analysis to investigate factors having influence on mobile banking adaption and their predictive ability. The study identified total five factors namely utility benefit, convenience benefit, social benefit, trust benefit, and behavioural benefit determining the adaption of mobile banking. All factors had a significant influence on adaptation intentions and could be used for prediction. Further, trust benefit was identified to have as strongest influence on the adaptation intentions..